(untitled) (Fiep Bulletin - online, 2025)
Introduction: Therefore, there is a need to encourage play among young people and adolescents, taking them away from screens, as they are being denied the opportunity to engage in physical activities. Additionally, poor eating habits are common. Data indicate that overweight/obesity is more prevalent among girls, even though the number of girls in the study was smaller compared to boys. The percentage of overweight girls is higher. Regardless of different socioeconomic conditions, both overweight and obesity have been increasing in recent years (NAHAS, 2017). Methodology: A field study was conducted with thirty-four volunteer students aged between 11 and 16 years. This study aimed to investigate the health of students concerning obesity. As part of the research, the following were observed: age, height, weight, BMI, abdominal circumference, and finally, a test developed by Nahas was applied. In this test, participants assessed their daily habits, indicating how healthy or sedentary they are. A measuring tape was used to determine height, and a 1.5-meter tape was used to measure abdominal circumference. Results: In the school environment, physical education plays a crucial preventive role, especially given the rise in childhood obesity. Research highlights that regular physical activity can significantly reduce the risk of obesity in children. Lack of movement and inadequate food consumption have led to an increase in morbidities such as hypertension and diabetes, in addition to compromising the physical and cognitive development of young people.